Acemannan-containing bioactive resin modified glass ionomer demonstrates satisfactory physical and biological properties - Thant Aye Aye; Sangvanich Polkit; Inchudech Klaijan; Kuvieng Nachanok; Lalitkanjanakul Salil; Thunyakitpisal Pasutha (Journal of Dental Sciences, 2024)
Background/purpose: Resin-modified glass ionomers (RMGIs) have been recommended as liner and cement to provide the teeth with mechanical support, a chemical barrier, and thermal insulation. Acemannan, the main polysaccharide extracted from Aloe vera, is a promising inductive material in vitro and in vivo. This study aimed to develop acemannan-containing bioactive resin-modified glass ionomers (RMGIs). Materials and methods: Acemannan (3%, 5%, and 10%) was added to the three types of RMGIs (RU-HBM1/Fuji II LC/Vitrebond) to generate 3%, 5%, and 10% aceRMGIs (aceRU/aceFuji/aceVB). The materials were evaluated for depth of cure/flexural strength/cumulative fluoride ion release. Cell viability and vascular endothelial growth factor (VEGF) and bone morphogenetic protein-2 (BMP-2) secretion were determined using MTT/apoptosis/necrosis assays, and ELISA kits, respectively. RMGI without acemannan were used as controls. Results: The aceRMGIs met the ISO requirements for depth of cure and flexural strength. Adding 10% acemannan increased the cumulative fluoride release in the RU and FJ groups, but slightly decreased it in the VB group (P < 0.05). The MTT assay revealed 10% aceRU and all aceFJ groups significantly increased cell viability compared with each control group (P < 0.05). Apoptosis/necrosis assay showed the biocompatibility of all aceRMGIs. Adding acemannan to RMGIs significantly induced VEGF expression in a dose dependent manner while 5% and 10% aceRU significantly induced BMP-2 expression compared with RU group (P < 0.05). Conclusion: We conclude that 5–10% acemannan in RMGI is the optimal concentration based on its physical properties and ability to induce pulp cell proliferation and growth factor secretion.